Building Customer Loyalty Through Relationship Marketing And Price At Motorcycle Washes In Palu City - I Kadek Rio Ardayana; Maskuri Sutomo; Zakiyah Zahara; Farid Farid (UNIVED Press, 2025)
This study aims to determine the effect of Relationship Marketing and Price on customer loyalty at Motorbike washing in Palu City This quantitative research was conducted at the Sula motorbike washing company in Vatutela, Palu City. The research was conducted from October to December 2024.This study involved 60 respondents and used the Roscoe method. Purposive sampling is a sampling method in which research is conducted on a group of subjects who have specific characteristics. Data were collected through interviews and distributing questionnaires to participants. This study used multiple linear regression as a data analysis technique and used the SPSS program as an analytical tool. According to the results of multiple linear regression analysis conducted in this study, it can be concluded that relationship marketing and price variables have an influence on customer loyalty at Sula Motor Wash, Palu City, both partially and simultaneously. This shows that proper pricing and relationship marketing strategies help build and maintain customer loyalty.